Video Tutorials in Teacher Education: Benefits, Difficulties, and Key Knowledge and Skills - Łukasz Tomczyk; Maria Lidia Mascia; Francisco David Guillen-Gamez (MDPI AG, 2023)
Shaping the competences of future teachers in a way that is appropriate to the current stage of development of the information society is, in the post-COVID era, a topical and important subject. The accumulation of experience in recent years with the use of digital edtech has forced the search for optimal solutions to support the learning and teaching process. Among such (still undervalued) solutions are video tutorials. This article answers the three research questions: (1) What are the benefits of using video tutorials in education? (2) What difficulties do future teachers face when creating educational tutorials? (3) What key knowledge and skills are required of teachers who wish to create video tutorials? The study (qualitative, based on structured interviews) involved 16 pre-service teachers (Poland) who attended a course on the introduction to the use of information technology in 2022/2023 at one of the leading academic universities in Poland. The collected data, showing the complexity of the use of this type of edtech, provide not only a simple diagnosis regarding the processes of creating and using video tutorials by future generations of teachers, but also allow for the modernisation of academic programmes that prepare pedagogical graduates to work in an increasingly digitalised world of education.